2022
DOI: 10.53889/ijbetsd.v2i1.131
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Guided Inquiry Learning Model Through the Utilization of School Environment Towards Students' Scientific Literacy on Biodiversity Concepts

Abstract: This research aimed to observe the effect of guided inquiry learning model through the utilization of school environment toward student scientific literacy on biodiversity concepts. This research  was a quasi-experimental research that using randomized control group, pretest-posttest design. The sampling technique used in this research was simple random sampling at one high school i Serag City, Indonesia with class X MIPA 5 as an experiment class and class X MIPA 4 as control class. The result of the scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Using learning media in teaching biodiversity offers several benefits in enhancing students' understanding and engagement with the subject. However, with the development of technology, both hardware and software, educators have a wide variety of media at their disposal for creating learning materials in biodiversity and biotechnology that can be tailored to students' requirements and classroom settings (Wahyuni et al, 2022).…”
Section: Rhizomementioning
confidence: 99%
“…Using learning media in teaching biodiversity offers several benefits in enhancing students' understanding and engagement with the subject. However, with the development of technology, both hardware and software, educators have a wide variety of media at their disposal for creating learning materials in biodiversity and biotechnology that can be tailored to students' requirements and classroom settings (Wahyuni et al, 2022).…”
Section: Rhizomementioning
confidence: 99%
“…(2021) implemented the biotechnology learning using pulau tunda's local potential, Sari et al (2022) conducted a systematic review on the implementation of bioinformatics learning in senior high school, Haryadi and Pujiastuti (2022) implemented STEM-PJBL model, Hendriyani et al (2023) used the project report through the STEM integrated project based learning model, and Widyastuti et al (2022) used discovery learning model through the aptitude treatment interaction (ATI). In the media learning, Baga et al (2021) used the comic media, Awaliyati et al (2021) developed the bacteria magz, Khastini et al (2022) developed the monopoly digestive media based on educational games, Wahyuni et al (2022b) developed the question card game, and Alya et al (2023) used the poster media, Syahfitri et al (2022) implemented the online learning using google classroom, Subagja et al (2022) conducted the student needs analysis of the scientific literacy oriented interactive multimedia, and Yuliani et al (2022) conducted a bibliometric analysis on mapping research on multimedia biology, Khastini et al (2023) implemented the estudent worksheets, and Ernawati and Sujatmika (2021) developed a worksheet based on a scientific approach. In the student learning outcomes, Fitriana et al (2022) analyzed the learning difficulties of class xii high school students and Yuliasari et al (2023) identified the students' misconceptions on the photosynthetic and plant respiration concepts using a two-tier diagnostic test.…”
Section: Introductionmentioning
confidence: 99%
“…The syntax of guided inquiry learning model according to Wahyuni et al (2022) is as follows posing questions or problems. In this case, students are instructed to identify a problem and place it on the board, then the teacher divides the class into several groups, formulating hypotheses.…”
Section: Introductionmentioning
confidence: 99%